Solar geometry and the organization of the annual cycle through architecture and the funerary landscape in Qubbet el Hawa - Joyanes Díaz, María Dolores; Martínez de Dios, Juan Luis; Mozas-Calvache, Antonio; Ruiz-Jaramillo, Jonathan; Muñoz-González, Carmen María; Jiménez Serrano, Alejandro (TT Publishing Limited, 2022)
The longitudinal axes of the Middle Kingdom tombs excavated in the necropolis of Qubbet el-Hawa were precisely oriented to the summer and winter solstices. Located on the western side of the Nile, opposite Elephantine Island, the architectural design of these tombs differed greatly from that of the Old Kingdom with elongated spaces around these axes in relation to the solar cycle. As architecture, was excavated from the landscape itself, the presence of the sun was decisive in letting light in through the single doorway, which acted as a transitional threshold to project the sunlight indoors. Funerary complex No.33 followed the longitudinal direction of the intersolstice axis. This important architectural construction of the necropolis reflects the evolution of a typical Upper Egyptian funerary model during the Middle Kingdom. Analysis of the illumination of the architectural space throughout the year confirms that the continuous movement of the sun during its cycle can be observed inside. The starting point of this analysis, is these spatial results, aiming to find an explanation for the geometric composition and specific design of the different architectural elements which make this a rounded, beautiful and harmonious complex. The QH33 funerary complex was built following very specific planning, which reworked and refined a model of a community which aimed to connect the celestial geometry to the geographical landscape through this architecture.
Keywords: Monumentos funerarios-Elefantina (Egipto); Egyptian architecture; Archaeology; Landscape; Solar geometry; Calendar; Middle Kingdom; Necropolis; Illumination; Solstice; Tombs; Sunlight; Elephantine; Sanctuary